(untitled) (Revista Contexto & Saúde, 2026)
Objective: to identify the knowledge that primary care health professionals have regarding integrative and complementary health practices and how these practices are provided. Method: A descriptive, exploratory study with a qualitative approach. Data were collected through semi-structured interviews with higher-education professionals from the core healthcare team—physicians and nurses—as well as the multidisciplinary home care and support team. The results were analyzed using Laurence Bardin’s content analysis technique. Results: It was found that professionals’ knowledge of Integrative and Complementary Health Practices and the National Policy on Integrative and Complementary Health Practices is limited and superficial, and that most had no prior exposure to the subject during their training, being unable to determine whether the municipality where they work offers any type of integrative practice. It was also found that the lack of training on the subject hinders the provision of these services. Conclusion: It is necessary to implement effective measures that promote training and investments in infrastructure and supplies so that healthcare professionals can provide high-quality care for the various practices already guaranteed by the National Policy on Integrative and Complementary Practices.